Genomic configuration of Bacillus subtilis (NMB01) unveils its antiviral activity against Orthotospovirus arachinecrosis infecting tomato - Gayathri, M.; Sharanya, R.; Renukadevi, P.; Malathi, Varagur Ganesan; Ghosh, Amalendu; Nallusamy, Saranya; Varanavasiappan, S.; Nakkeeran, S.; Alkahtani, Saad (Frontiers in Plant Science, 2025)
Orthotospovirus arachinecrosis (groundnut bud necrosis virus, GBNV) infecting tomato is a devastating viral pathogen responsible for severe yield losses of up to 100%. Considering the significance of the plant growth-promoting bacteria to induce innate immunity, attempts were made to evaluate the antiviral efficacy of Bacillus subtilis NMB01 against GBNV in cowpea and tomato. Foliar application of B. subtilis NMB01 at 1.5% onto the leaves of cowpea and tomato followed by challenge inoculation with GBNV significantly reduced the incidence of GBNV from 80% to 90% in response to the untreated inoculated control. Hence, we had a quest to understand if any genes were contributing toward the suppression of GBNV in assay hosts. To unveil the secrecy, whole-genome sequencing of B. subtilis NMB01 was carried out. The genome sequence of NMB01 revealed the presence of secondary metabolite biosynthetic gene clusters, including non-ribosomal peptide synthetases (NRPSs) and polyketide synthases (PKSs) which also encoded bacteriocins and antimicrobial peptides. The pan-genome analysis identified 1,640 core genes, 4,885 dispensable genes, and 60 unique genes, including MAMP genes that induce host immune responses. Comparative genome and proteome analysis with other genomes of B. subtilis strains in a public domain through OrthoVenn analysis revealed the presence of 4,241 proteins, 3,695 clusters, and 655 singletons in our study isolate. Furthermore, the NMB01-treated tomato plants increased the levels of defense-related genes (MAPKK1, WRKY33, PR1, PAL, and NPR1), enhancing immune system priming against GBNV infection. These findings suggest that B. subtilis NMB01 can be used as a promising biological control agent for managing plant viral disease sustainably.